Prevalence of Anemia Among Children in a Single University Hospital - Neslihan Karakurt; Özlem Terzi (Galenos Publishing House, 2019)
INTRODUCTION: Anemia is a common public health issue, causing an increase in mortality and morbidity, especially in pregnant women and children. WHO reported the prevalence of anemia in preschool children as 47.4%. Iron deficiency is responsible for approximately 50% of cases with anemia. This study aims to determine the prevalence of anemia and the underlying causes of anemia in pediatric patients who were admitted to the reference hospital. METHODS: This cross-sectional study was planned retrospectively and children between 0.5-15 years of age who were admitted to our hospital for any reason between July 2017-July 2018 were included. Sampling included those with anemia, hemoglobin value less than 11 g/dl. RESULTS: The incidence of anemia was 8.2%(n=4655). The median age of anemic children was three years, and 54.4% were male. Anemia was more common among 2-5 year-old-children (50.8%). The prevalence of anemia was higher in boys at age of 0.5-1 and 2-5 years old, while it was higher in girls at age of 10-12 years and 13-15 years old, and the difference was statistically significant. The median hemoglobin was 10.2(min-max: 2.8-10.9)g/dl, MCV was 74.5(min-max: 46.9-126.8)fl. DISCUSSION AND CONCLUSION: The incidence of anemia in a reference centre in Black Sea region of Turkey at 0.5- 15 years of age is 8%. The laboratory parameters were consistent with a probable diagnosis of iron deficiency anemia. The majority of patients(64%) had mild anemia. Physicians dealing and cooperating with parents in the prevention and treatment of anemia is critical in protecting children from anemia, which is a reason of preventable mental retardation.